Allergic contact dermatitis to antibacterial agents - Gorgievska-Sukarovska, Biljana (Array, 2009)
Summary: Topical antibiotics are frequently introduced in therapy by various specialists, e.g., dermatologists-venereologists, ENT specialists, proctologists, ophthalmologists, and others. In dermatology, topical antibiotics are used in the treatment of superficial inflammatory skin lesions, acne and rosacea. These agents are also used in the prevention of inflammatory lesions after surgical and corrective procedures. Long-term and uncontrolled application of topical antibiotics, on the skin with impaired protective barrier in particular, implies a risk for the development of hypersensitivity to these agents. Considering the very wide utilization of these agents, hypersensitivity to topical antibiotics poses a major problem worldwide.The groups at a high risk of contact sensitivity to topical antibiotics include patients with chronic venous insufficiency, chronic ulcers and chronic otitis externa, as well as individuals at occupational exposure to antibiotics, e.g., human medicine and veterinary medicine professionals, pharmaceutical industry workers, cattle breeders, etc. When longterm therapy fails to result in improvement in the above mentioned chronic states, the possibility of allergic reactions to topical agents should be taken in consideration. Cross-sensitivity, which is frequently associated with the use of topical aminoglycoside antibiotics, poses a significant problem